The general equation for a quadratic equation is,
![y=ax^2+bx+c](https://img.qammunity.org/2023/formulas/mathematics/high-school/g7mvpjunjwe6qob7ddy7l4f0glbtdi9gci.png)
Substititute the values to obtain the equations for the coefficients.
![\begin{gathered} 2=a(-1)^2+(-1)b+c \\ a-b+c=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qd1f10u1vbwb9ak9jryin1ugzb1s23dva7.png)
![\begin{gathered} 1=a(0)^2+b(0)+c \\ c=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hvmhwwcgmj70ghpqvuabwckp0vkp5yqk2e.png)
and
![\begin{gathered} 5=a(-2)^2+b(-2)+c \\ 4a-2b+c=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/v6rgu0ydvzo3ee680apu30jvhb6lvauv3f.png)
Substitute the value of c in the equation a-b+c=2 to obtain the equation for a and b.
![\begin{gathered} a-b+1=2 \\ a=1+b \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/s8lm6sf3ig8aw4gadm0io9bgb2h8gy8cgi.png)
Substitute the value of a and c in the equation 4a-2b+c=5 to obtain the value of b.
![\begin{gathered} 4(1+b)-2b+1=5 \\ 4-2b+1=5 \\ 2b=0 \\ b=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/b5080dx0m4nyih92chjtux6td8uc3qe00w.png)
Substitute the value of b in the equation a=1+b to obtain the value of a.
![\begin{gathered} a=1+0 \\ a=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bg28jb9ha9vwp85vty6wukdbdp0ac78n8u.png)
So quadratic equation for a=1, b=0 and c=1 is,
![y=x^2+1](https://img.qammunity.org/2023/formulas/mathematics/college/vipdgpbp8rpv9l3j8korvnkwawo0ppkybz.png)